Effectiveness of the Discrete Trial Training Method for Improving Receptive Language Skills in Children with Autism Spectrum Disorder (ASD) At Al-Fatih Center - Salsa Aulia; Virginia Hanandita; Sinar Perdana Putra (Sean Institute, 2025)
Children with Autism Spectrum Disorder (ASD) often experience difficulties in receptive language, which affects their daily communication. This study aims to examine the effectiveness of the Discrete Trial Training (DTT) method in improving receptive language skills of children with ASD. The research employed an experimental design using One Group Pretest-Posttest with a sample of six children aged 5 years at Al-Fatih Center. The Receptive Verbal Vocabulary Test (TKV-R), validated and reliable in Indonesia, was used as the measurement instrument. The intervention consisted of 12 sessions, and data were analyzed using Wilcoxon Signed Rank Test. The results showed a significant improvement in receptive language, with the mean score increasing from 1.33 (SD = 2.066) at pretest to 10.00 (SD= 0.00) at posttest (p = 0.023). These findings clearly indicate that DTT is effective in achieving the research objective of enhancing receptive language skills in children with ASD, particularly in improving their ability to follow instructions and identify objects appropriately.